2005
DOI: 10.1590/s0074-02762005000200013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania braziliensis in human paraffin-embedded tissues from Tucumán, Argentina by polymerase chain reaction

Abstract: American cutaneous leishmaniasis (ACL) is an endemic disease in Northern Key words: Leishmania (V.) braziliensis -diagnosis -polymerase chain reaction -ArgentinaAmerican tegumentary leishmaniasis (cutaneous and mucocutaneous) has been endemic in Argentina since 1916(Mazza 1926. In the Northern provinces of the country, outbreaks were identified in 1985/1987, 1997/1998. In Tucumán province, between 1991and 1996 leishmaniasis cases were reported (Marcolongo et al. 1993, Yadón 1997, Villalonga 1998.In the America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Previous works has demonstrated that paraffin-embedded tissues are suitable for DNA extraction and for some downstream molecular methods [1116]. Thus, the aim of this study was to detect Leishmania infantum by PCR in paraffin-embedded lung tissue from naturally infected Brazilian dogs and to compare the results with those from histological and immunohistochemical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works has demonstrated that paraffin-embedded tissues are suitable for DNA extraction and for some downstream molecular methods [1116]. Thus, the aim of this study was to detect Leishmania infantum by PCR in paraffin-embedded lung tissue from naturally infected Brazilian dogs and to compare the results with those from histological and immunohistochemical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This hyper-endemic area had 66.4% of the ACL cases already in 1930 (Bernasconi 1930), but also recorded the first epidemic outbreak of ACL in Argentina during 1984-1985(Sosa-Estani et al 2000, and the largest outbreak ever observed in the country with more than 900 clustered cases in 1998 (Salomón et al 2001). Leishmania (Viannia) braziliensis was isolated from human cases during the outbreaks (Segura et al 2000, Cordoba-Lanus et al 2005, and Lutzomyia neivai was incriminated as its main vector (Cordoba-Lanus et al 2006). The prevalence and distribution of Lu.…”
mentioning
confidence: 99%
“…Previous studies have shown the possibility of extracting amplifiable DNA of Leishmania from dried or old materials, including archival air-dried unstained BM slides or Giemsa-stained slides (Brustolini et al , 2007), blood or BM aspirates spotted onto filter paper (Cortes et al , 2004; Da Silva et al , 2004), and even paraffin-embedded tissues (Lanús et al , 2005) or formalin-fixed material (Gebhardt et al , 2015). Slide smears are easily stored, do not require special storage conditions and can be kept at room temperature.…”
Section: Discussionmentioning
confidence: 99%